Significance of viscosity and thermal conductivity variation parameters on the dynamics of Newtonian fluid conveying tiny particles over a convectively heated surface - O.A. Famakinwa; O.K. Koriko; K.S. Adegbie; A.J. Omowaye (Partial Differential Equations in Applied Mathematics, 2021)
The significance of viscosity and thermal conductivity variation parameters on the dynamics of Newtonian fluid conveying tiny particles over a convectively heated surface is examined. The dimensional partial differential equations controlling the flow are remodeled to ordinary differential equations via suitable similarity variables in conjunction with the rescaled Nusselt, Sherwood and density number of motile microorganisms. The resulting nonlinear coupled ordinary differential equations are consequently scaled down to a system of first order ordinary differential equations. The system of equations are evaluated arithmetically via shooting technique along with fourth order Runge–Kutta integration scheme for different boundary conditions. The result was found to be in excellent agreement when compared with available records in the literature. The major highlights of the problem are analyzed and discussed thoroughly. It is seen that increase in viscosity variation parameter is capable to cause a decline in the local skin friction coefficients at the rate of −0.04985and the Nusselt number is an increasing function of the thermal conductivity variation parameter.